PROBLEMATIKA PEMBERIAN KREDIT BERDASARKAN AGUNAN BERSTATUS SK CAMAT DAN COVER NOTE NOTARIS (STUDI KASUS PADA PT. BANK RAKYAT INDONESIA (PERSERO), TBK CABANG LUBUK PAKAM - WINA FEBRIANI (PREMISE LAW JURNAL, 2017)
People knoe thw credit in everyday language as debit. Steps that are not less impotant in obtaining the certainty of debt repayment, a guarantee is required as a condition of credit application. The bonds of collateral in the term of immovable objects may only be done on the land with the status of certificate of property. To collateral which is a certificate of Camat can’t be bound by the deposit rights and the problem is when the sub-district head’s certificate fails to be upgraded to a certificate and can’t be executed through the auction. Then BRI branch Lubuk PAkam will conduct a civil suit to be able to execute the collateral.Keyword : Collateral which status is indicated by SK (the letter of notification) fromthe head of district